2007
DOI: 10.1017/s0956792507007140
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of vortex dynamics in Ginzburg-Landau-Schrödinger equation

Abstract: The rich dynamics of quantized vortices governed by the Ginzburg-Landau-Schrödinger equation (GLSE) is an interesting problem studied in many application fields. Although recent mathematical analysis and numerical simulations have led to a much better understanding of such dynamics, many important questions remain open. In this article, we consider numerical simulations of the GLSE in two dimensions with non-zero far-field conditions. Using twodimensional polar coordinates, transversely highly oscillating far-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 48 publications
3
48
0
1
Order By: Relevance
“…Different steady state patterns of vortex lattices under the GLE dynamics were obtained numerically. From our numerical results, we observed that boundary conditions and domain geometry affect significantly on vortex dynamics and interaction, which showed different interaction patterns compared to those in the whole space case [37,38]. tion of Singapore grant R-146-000-120-112.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Different steady state patterns of vortex lattices under the GLE dynamics were obtained numerically. From our numerical results, we observed that boundary conditions and domain geometry affect significantly on vortex dynamics and interaction, which showed different interaction patterns compared to those in the whole space case [37,38]. tion of Singapore grant R-146-000-120-112.…”
Section: Resultsmentioning
confidence: 81%
“…In this case, it is natural to adopt the polar coordinate (r,θ) in our numerical discretization. In order to discretize (3.2) with either (1.3) or (1.4), we apply the standard Fourier pseudospectral method in θ-direction [34], finite element method in r-direction, and Crank-Nicolson method in time [4,5,37]. Plugging the following truncated Fourier expansion for ψ ε ψ ε (r,θ,t) =…”
Section: Discretization When ω Is a Diskmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most well-studied equations in nonlinear science is the Ginzburg-Landau-Schrödinger equation (GLSE) of the form [36] (α − iβ)∂ t ψ(x, t) = ∇ 2 ψ + 1 ε 2 V (x) − |ψ| 2 ψ, x ∈ R 2 , t > 0, (1.1)…”
Section: Introductionmentioning
confidence: 99%
“…As an additional example to test the MSD boundary condition, we simulate two equal-charge vortices whose interaction is known to produce a rotating circular motion of the two vortices orbiting each other [11,33,44,45]. Using a fixed grid size of 171 × 171, the simulations are run for long times using the L0 and MSD boundary conditions.…”
Section: Two-dimensional Dark Vortices In the Nlsementioning
confidence: 99%